PELAKSANAAN COMPULSORY LICENSING PATEN OBAT-OBATAN BIDANG FARMASI DI INDONESIA DIKAITKAN DENGAN DOHA DECLARATION ON THE TRIPS AGREEMENT AND PUBLIC HEALTH - Samariadi Samariadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Purpose of this study is firstly to find out implementation of compulsory licensing patent medicines in Indonesia’s pharmaceutical field linked Declaration DOHA, secondly to know resistance implementation of compulsory licensing to access drug in Indonesia, thirdly to know efforts should be done in implementation compulsory licensing as to support access public health. Author used legal research methods to get the result. Results of formulation problem, it can be concluded that, firstly implementation of compulsory licensing in Indonesia is still not maximized because only implement patent by the government alone, secondly obstacles in the implementation of covering obstacles in  juridical aspect and non-juridical, thirdly attempts that should be done is to implement both compulsory licensing program which has been legalized by Indonesian patent legislation. Advice from author, firstly there should be legal reforms in Act Patent to enhance the article fully support access to public health, secondly their efforts to optimize pharmaceutical industry through appointment of other pharmaceutical industry to produce drugs Antiretroviral besides chemical pharma, thirdly government should enhance further technical provisions of compulsory licensing programs such as compulsory licenses, in order to assist the government to implement the mandate of the 1945 task in fulfilling rights of all people.